Thermal insulation protective material for disaster recovery memory and preparation method thereof
By developing nanocomposite materials, combining porous structural materials and phase change energy storage materials, the problems of insufficient insulation performance and excessive weight in vehicle applications are solved, and thermal insulation protection materials with efficient insulation, mechanical strength and flame retardant performance are achieved, effectively protecting the vehicle disaster recovery memory in a high-temperature environment.
Patent Information
- Application Number
- CN202411839122.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional thermal insulation materials have insufficient thermal insulation performance and excessive weight in vehicle applications, making it difficult to effectively protect vehicle disaster recovery memory in high temperature environments.
A nanocomposite material was developed, and by introducing materials such as diatomaceous earth, vapor-phase nanosilica, calcium hydroxide, etc., combined with autoclave maintenance technology and phase change energy storage materials, a thermal insulation protection material with high efficiency insulating, mechanical strength and flame retardant performance was formed.
It achieves excellent thermal insulation performance, effectively blocks high-temperature conduction, keeps the internal temperature of the memory within a safe range, and has a lightweight design, excellent mechanical strength and flame retardant performance, ensuring effective protection of the memory in various extreme environments.
Smart Images

Figure CN119661153A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electronic device protection, and in particular relates to a heat-insulating protective material for a disaster recovery storage device and a preparation method thereof. Background Art
[0002] In the field of modern transportation, the safety and reliability of vehicles occupy a core position. With the acceleration of the process of vehicle intelligence, especially for "two passenger and one dangerous goods" vehicles, vehicle disaster recovery storage, as a core device for storing key information, is becoming more and more important when the vehicle encounters an accident or disaster. Therefore, thermal insulation and protective materials are crucial to ensure the safety of vehicle disaster recovery storage.
[0003] With the rapid development of automotive technology, the potential risks faced by vehicles are becoming increasingly complex and diverse. Traffic accidents, fires, extreme high temperature environments and other factors may pose a serious threat to vehicle disaster recovery memory. In traffic accidents, the high temperature caused by severe impacts and vehicle deformation can easily damage the memory; and in fire scenes, high temperature flames pose a huge challenge to the memory. In addition, in hot climates or long-term driving conditions, the rise in temperature inside the vehicle may also have an adverse effect on the memory. In view of this, the development of efficient thermal insulation and protective materials has become a top priority. Traditional thermal insulation materials face many limitations in vehicle applications, such as insufficient thermal insulation performance and excessive weight, which make it difficult to meet actual needs. Summary of the invention
[0004] The thermal insulation and protective material for the vehicle disaster recovery storage device involved in the present invention is intended to overcome these limitations. The material has excellent thermal insulation properties, can effectively block high temperature conduction, and ensure that the internal temperature of the storage device is maintained within a safe range. At the same time, the material realizes a lightweight design, reduces the burden on the vehicle, and is easy to install and use. In addition, the material also exhibits excellent mechanical strength and stability, and can ensure effective protection of the storage device even when the vehicle is subjected to impact and vibration. To achieve the above goals, the present invention makes full use of the unique properties of nanomaterials to develop nanocomposites with high efficiency thermal insulation and mechanical strength. By introducing porous structural materials such as diatomaceous earth, not only the thermal insulation effect is improved, but also the weight and cost of the material are reduced. At the same time, the introduction of phase change energy storage materials further enhances the energy storage performance of the product. In terms of flame retardant properties, the materials selected in the present invention all have flame retardant effects, ensuring that in extreme cases such as fire, the thermal insulation and protective materials will not burn or release harmful gases, thereby fully protecting the safety of the vehicle disaster recovery storage device.
[0005] The invention discloses a heat-insulating protective material for a disaster recovery storage device and a preparation method thereof. The heat-insulating material is composed of the following raw materials in percentage by mass: 20-25 parts of diatomaceous earth, 15-20 parts of fumed nano-silicon dioxide, 10-12 parts of calcium hydroxide, 4-6 parts of white cement, 15-25 parts of copper sulfate pentahydrate, 15-25 parts of magnesium chloride hexahydrate, 2-3 parts of glass fiber, and 1-2 parts of polycrystalline mullite fiber.
[0006] The method for preparing the heat-insulating protective material comprises the following steps:
[0007] a) Fiber dispersion: by weight, take 4-6 parts of white cement, 2-3 parts of glass fiber, and 1-2 parts of polycrystalline mullite fiber, mix the raw materials and send them into a forced mixer, mix them evenly and set aside;
[0008] b) Mixing raw materials: by weight, 20-25 parts of diatomaceous earth, 15-20 parts of fumed nano-silicon dioxide, 10-12 parts of calcium hydroxide, 15-25 parts of copper sulfate pentahydrate, and 15-25 parts of magnesium chloride hexahydrate are sent to a forced mixer and stirred evenly with the dispersed fibers, and then set aside after mixing evenly;
[0009] c) Raw material aging: put the mixed raw materials into a sealed bag, seal and store for later use;
[0010] d) Molding: feeding the aged raw materials into the mold and pressing the raw materials into the required green body;
[0011] e) Autoclave curing: The formed green body and the mold are sent into an autoclave reactor, heated and cured for a certain period of time, so that the siliceous raw materials in the green body react with the calcium raw materials to form tobermorite, and at the same time promote the hardening of cement to form the basic strength of the product;
[0012] f) Drying: Dry the product after autoclave curing to remove free moisture in the product;
[0013] g) Surface isolation: Spray isolation paint on the surface of the dried product to prevent the product from weathering.
[0014] Preferably, in step a), the length of the glass fiber is 3-5 mm, the length of the polycrystalline mullite fiber is <1 mm, and the forced mixer needs to run the reamer for 15-30 minutes.
[0015] Further preferably, in step b), the moisture content of diatomaceous earth needs to be controlled between 10-20%, the particle size of copper sulfate pentahydrate needs to be less than 100 mesh, the particle size of magnesium chloride hexahydrate needs to be less than 100 mesh, and the forced stirring time is 10-20 minutes.
[0016] More preferably, the container needs to be kept sealed during aging in step c), the aging temperature is less than 35° C., and the aging time is 24-36 hours.
[0017] More preferably, in step d), the molding pressure needs to be controlled within 10-20 MPa, and the holding time needs to be controlled within 12-24 hours.
[0018] More preferably, in step e), the temperature of the autoclaved oxidation should be controlled at 80-100° C., and the oxidation time should be controlled at 4-10 hours.
[0019] More preferably, in step f), the drying temperature is 60-80° C. and the drying time is 1-2 hours.
[0020] More preferably, the isolation varnish in step g) is an epoxy resin isolation varnish.
[0021] This invention exploits the unique advantages of fumed nano-silicon dioxide, which has excellent thermal insulation properties and its extremely low thermal conductivity fundamentally ensures the thermal insulation performance of the product. On this basis, by introducing porous materials such as diatomaceous earth, the rich nano-scale pore structure contained in diatomaceous earth not only significantly enhances the thermal insulation effect, but also achieves the dual goals of material lightweighting and cost control.
[0022] In addition, the addition of calcium hydroxide combined with the autoclave curing process not only promotes the formation of tobermorite (a material with extremely low thermal conductivity) between gas-phase nano-silicon dioxide and diatomaceous earth, but also significantly increases the hardening rate of cement, laying the foundation for the basic strength of the product. In addition, the innovative introduction of phase change energy storage materials has greatly enhanced the energy storage and regulation capabilities of the product.
[0023] In terms of safety, all materials selected for this solution exhibit excellent flame retardant properties and can maintain stability in extreme environments such as fire, preventing thermal insulation materials from burning or releasing harmful gases, thus providing impeccable protection for the comprehensive safety of the vehicle disaster recovery storage device. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the structure of the disaster recovery storage device of the present invention;
[0025] Figure 2 This is a schematic diagram of the use of the protective material of the present invention to prepare a disaster recovery storage device;
[0026] Figure 3 These are pictures from the thermal assessment site. DETAILED DESCRIPTION
[0027] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0028] Example 1
[0029] A thermal insulation protective material for disaster recovery storage and a preparation method thereof are prepared according to the following steps:
[0030] a) Fiber dispersion: Take 6 parts of white cement, 3 parts of glass fiber, and 1 part of polycrystalline mullite fiber by weight, mix the raw materials and send them into a forced mixer, start the reamer to stir for 30 minutes, and mix them evenly for standby use;
[0031] b) Mixing raw materials: by weight, 20 parts of diatomaceous earth, 20 parts of fumed nano-silicon dioxide, 10 parts of calcium hydroxide, 15 parts of copper sulfate pentahydrate, and 25 parts of magnesium chloride hexahydrate are sent to a forced mixer and stirred together with the dispersed fibers for 10 minutes. After mixing evenly, they are set aside for use;
[0032] c) Raw material aging: put the mixed raw materials into a sealed bag, seal and store for 24 hours for later use;
[0033] d) Molding: The aged raw materials are fed into the mold, the molding pressure is 15MPa, the pressure is maintained for 24 hours, and the raw materials are pressed into the required green body;
[0034] e) Autoclave curing: The formed green body and the mold are placed in an autoclave reactor, heated to 100°C and cured for 8 hours to allow the siliceous raw materials in the green body to react with the calcium raw materials to form tobermorite, while promoting cement hardening to form the basic strength of the product;
[0035] f) Drying: Dry the product after autoclave curing at 60°C for 1.5 hours to remove free moisture in the product;
[0036] g) Surface isolation: Spray isolation paint on the surface of the dried product to prevent the product from weathering.
[0037] Example 2
[0038] A thermal insulation protective material for disaster recovery storage and a preparation method thereof are prepared according to the following steps:
[0039] a) Fiber dispersion: Take 4 parts of white cement, 2 parts of glass fiber, and 2 parts of polycrystalline mullite fiber by weight, mix the raw materials and send them into a forced mixer, start the reamer to stir for 15 minutes, and mix them evenly for standby use;
[0040] b) Mixing raw materials: by weight, 22 parts of diatomaceous earth, 18 parts of fumed nano-silicon dioxide, 12 parts of calcium hydroxide, 20 parts of copper sulfate pentahydrate, and 20 parts of magnesium chloride hexahydrate are sent to a forced mixer and stirred together with the dispersed fibers for 20 minutes. After mixing evenly, they are set aside for use;
[0041] c) Raw material aging: put the mixed raw materials into a sealed bag, seal and store for 36 hours for later use;
[0042] d) Molding: The aged raw materials are fed into the mold, the molding pressure is 20MPa, the pressure is maintained for 12 hours, and the raw materials are pressed into the required green body;
[0043] e) Autoclave curing: The formed green body and the mold are placed in an autoclave reactor, heated to 80°C and cured for 10 hours to allow the siliceous raw materials in the green body to react with the calcium raw materials to form tobermorite, while promoting cement hardening to form the basic strength of the product;
[0044] f) Drying: Dry the product after autoclave curing at 80°C for 1 hour to remove free moisture in the product;
[0045] g) Surface isolation: Spray isolation paint on the surface of the dried product to prevent the product from weathering.
[0046] Example 3
[0047] A thermal insulation protective material for disaster recovery storage and a preparation method thereof are prepared according to the following steps:
[0048] a) Fiber dispersion: Take 4 parts of white cement, 2 parts of glass fiber, and 2 parts of polycrystalline mullite fiber by weight, mix the raw materials and send them into a forced mixer, start the reamer to stir for 20 minutes, and mix them evenly for standby use;
[0049] b) Mixing raw materials: by weight, 25 parts of diatomaceous earth, 15 parts of fumed nano-silicon dioxide, 12 parts of calcium hydroxide, 25 parts of copper sulfate pentahydrate, and 15 parts of magnesium chloride hexahydrate are sent to a forced mixer and stirred together with the dispersed fibers for 15 minutes. After mixing evenly, they are set aside for use;
[0050] c) Raw material aging: put the mixed raw materials into a sealed bag, seal and store for 24 hours for later use;
[0051] d) Molding: The aged raw materials are fed into the mold, the molding pressure is 15MPa, the pressure is maintained for 20 hours, and the raw materials are pressed into the required green body;
[0052] e) Autoclave curing: The formed green body and the mold are placed in an autoclave reactor, heated to 100°C and cured for 8 hours to allow the siliceous raw materials in the green body to react with the calcium raw materials to form tobermorite, while promoting cement hardening to form the basic strength of the product;
[0053] f) Drying: Dry the product after autoclave curing at 70°C for 1.5 hours to remove free moisture in the product;
[0054] g) Surface isolation: Spray isolation paint on the surface of the dried product to prevent the product from weathering.
[0055] Example 4
[0056] A thermal insulation protective material for disaster recovery storage and a preparation method thereof are prepared according to the following steps:
[0057] a) Fiber dispersion: Take 5 parts of white cement, 2.5 parts of glass fiber, and 1.5 parts of polycrystalline mullite fiber by weight, mix the raw materials and send them into a forced mixer, start the reamer to stir for 30 minutes, and mix them evenly for standby use;
[0058] b) Mixing raw materials: by weight, 23 parts of diatomaceous earth, 17 parts of fumed nano-silicon dioxide, 11 parts of calcium hydroxide, 20 parts of copper sulfate pentahydrate, and 15 parts of magnesium chloride hexahydrate are sent to a forced mixer and stirred together with the dispersed fibers for 20 minutes. After mixing evenly, they are set aside for use;
[0059] c) Raw material aging: put the mixed raw materials into a sealed bag, seal and store for 36 hours for later use;
[0060] d) Molding: The aged raw materials are fed into the mold, the molding pressure is 10MPa, the pressure is maintained for 18 hours, and the raw materials are pressed into the required green body;
[0061] e) Autoclave curing: The formed green body and the mold are placed in an autoclave reactor, heated to 100°C and cured for 4 hours to allow the siliceous raw materials in the green body to react with the calcium raw materials to form tobermorite, while promoting cement hardening to form the basic strength of the product;
[0062] f) Drying: Dry the product after autoclave curing at 60°C for 2 hours to remove free moisture in the product;
[0063] g) Surface isolation: Spray isolation paint on the surface of the dried product to prevent the product from weathering.
[0064] Performance Test Table
[0065]
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A heat-insulating protective material for disaster recovery storage, characterized in that: The invention comprises the following components by weight: 20-25 parts of diatomaceous earth, 15-20 parts of fumed nano-silicon dioxide, 10-12 parts of calcium hydroxide, 4-6 parts of white cement, 15-25 parts of copper sulfate pentahydrate, 15-25 parts of magnesium chloride hexahydrate, 2-3 parts of glass fiber and 1-2 parts of polycrystalline mullite fiber.
2. A method for preparing a heat-insulating protective material for a disaster recovery storage device, characterized in that: The steps include: a) Fiber dispersion: by weight, take 4-6 parts of white cement, 2-3 parts of glass fiber, and 1-2 parts of polycrystalline mullite fiber, mix the raw materials and send them into a forced mixer, mix them evenly and set aside; b) Mixing raw materials: by weight, 20-25 parts of diatomaceous earth, 15-20 parts of fumed nano-silicon dioxide, 10-12 parts of calcium hydroxide, 15-25 parts of copper sulfate pentahydrate, and 15-25 parts of magnesium chloride hexahydrate are sent to a forced mixer and stirred evenly with the dispersed fibers, and then set aside after mixing evenly; c) Raw material aging: put the mixed raw materials into a sealed bag, seal and store for later use; d) Molding: feeding the aged raw materials into the mold and pressing the raw materials into the required green body; e) Autoclave curing: The formed green body and the mold are sent into an autoclave reactor, heated and cured for a certain period of time, so that the siliceous raw materials in the green body react with the calcium raw materials to form tobermorite, and at the same time promote cement hardening to form the basic strength of the product; f) Drying: Dry the product after autoclave curing to remove free moisture in the product; g) Surface isolation: Spray isolation paint on the surface of the dried product to prevent the product from weathering.
3. The method for preparing a heat-insulating protective material for a disaster recovery storage device according to claim 2, characterized in that: In step a), the length of the glass fiber is 3-5 mm, the length of the polycrystalline mullite fiber is <1 mm, and the forced mixer needs to run the reamer for 15-30 minutes.
4. The method for preparing a heat-insulating protective material for a disaster recovery storage device according to claim 2, characterized in that: In step b), the moisture content of diatomaceous earth needs to be controlled between 10-20%, the particle size of copper sulfate pentahydrate needs to be less than 100 mesh, the particle size of magnesium chloride hexahydrate needs to be less than 100 mesh, and the forced stirring time is 10-20 minutes.
5. The method for preparing a heat-insulating protective material for a disaster recovery storage device according to claim 2, characterized in that: In step c), the container needs to be kept sealed during aging, the aging temperature is less than 35° C., and the aging time is 24-36 hours.
6. The method for preparing a heat-insulating protective material for a disaster recovery storage device according to claim 2, characterized in that: In step d), the molding pressure needs to be controlled within 10-20 MPa, and the holding time needs to be controlled within 12-24 hours.
7. The method for preparing a heat-insulating protective material for a disaster recovery storage device according to claim 2, characterized in that: In step e), the temperature of the autoclave should be controlled at 80-100° C., and the oxidation time should be controlled at 4-10 hours.
8. The method for preparing a heat-insulating protective material for a disaster recovery storage device according to claim 2, characterized in that: In step f), the drying temperature is 60-80° C. and the drying time is 1-2 hours.
9. The method for preparing a heat-insulating protective material for a disaster recovery storage device according to claim 2, characterized in that: In step g), the isolation varnish is epoxy resin isolation varnish.